Attitudes of Police Recruits Toward Offenders: The Impact of the Police Training on Attitudinal Change - Cunha, Olga Cecília Soares da (2022)
The traditional prevailing perspectives on attitudes assume that attitudes, once formed, are relatively stable over time. However, research has revealed that attitudes may be influenced by different factors that may contribute to change them. The present longitudinal study aims to understand if the police recruits’ attitudes towards offenders change after police training. Besides, we aim to understand the impact of sociodemographic and personality variables on recruits’ attitudes towards offenders and which variables predict recruits’ attitudes. The Attitude Scale towards Offenders (ATO) and the NEO-FFI Personality Inventory were used in a sample of 74 recruits of a Portuguese Police Force - Guarda Nacional Republicana -, in two distinct moments (at the beginning and at the end of the police training programme). Results revealed that at the end of the training recruits hold more negative attitudes towards offenders. Those who had previous professional experience in the army hold more positive attitudes, but only at the beginning of the training. Only attitudes towards offenders at the beginning of the police training predict recruits’ attitudes towards offenders at the end of the training. These results emphasize the importance of initial and continuous training of recruits and police officers, especially in terms of their attitudes towards offenders.